Perlindungan Hukum Dari Negara Terhadap Notaris Yang Diakui Sebagai Officium Nobile - Nurarifah, Raden Ajeng Herning; Hakim, Luqman (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The aim of this research is to analyze and answer what form of legal protection the State provides for a Notary who is recognized as officium nobile. The research method used is legal research with a normative juridical approach. The results of this research show that the form of legal protection from the State consists of protection from the Law on the Position of Notaries, protection from the organization namely the Indonesian Notary Association (INI), having and being obliged to deny the right of rebuttal in the judicial process and keeping the contents of the deed and all information contained in it confidential. in it, and related to the Implementation of the Principle of Recognizing Service Users, where in these forms of protection there are still gaps or voids related which must be seriously taken into attention and consideration by the State to accomplish the legal protection for a Notary who is recognized as officium nobile.